Factors associated with men’s skincare sales at Shopee Indonesia e-commerce - Effendi, Muhamad H.; Mulyono, Lalu E.H (Pharmacology and Clinical Pharmacy Research, 2025)
Men's skincare use is increasing, along with the awareness of its importance. Shopee, as one of the largest e-commerce platforms in Indonesia, has become the main place for purchasing men's skincare products. However, study on the factors influencing men's skincare sales at e-commerce is still limited. This research aims to identify the factors associated with men's skincare sales at Shopee Indonesia e-commerce. A cross-sectional study, utilizing data from the 100 best-selling men's skincare products on Shopee until September 2024, was conducted. The dependent variable is the number of men's skincare sales, and the independent variables are the number of reviews, type of store, type of product, active ingredients, brand ambassador, number of products in one package, rating, price, free shipping feature, and discount. We analyzed the data using univariate descriptive, bivariate chi-square, and multivariate logistic regression analysis. SPSS 25 was used for all statistical analyses. The bivariate analysis results indicate that the number of reviews, product type, and rating have a significant relationship with men's skincare sales (p-values of p=0.000, p=0.076, and p=0.020). The logistic regression test showed that the variable number of reviews is the only variable that has a significant value with men's skincare sales (OR value of 132.021; CI=28.076-620.801; p=0.000). Thus, it can be concluded that the most associated factor with men's skincare sales at Shopee Indonesia's e-commerce until September 2024 is the number of reviews. Products with 376 or more reviews tend to have 132 times higher sales than products with fewer than 376 reviews.